Chemical modification of sesenduk [Endospermum diadenum (Miq.) airy shaw] wood with low molecular weight phenol formaldehyde - Purba, Tri Padukan (2012)
Low-density wood, sesenduk (Endospermum diadenum) has great a potential to substitute commercial timber, if its properties can be improved. One of the potential processes to enhance the properties of this timber is through bulking treatment with phenolic resin and rendered them insoluble in the wood. The objective of this study was to enhance the properties of sesenduk wood through bulking treatment with low molecular weight phenol formaldehyde (LmwPF, Mw = 600). The effect of initial moisture content (MC), duration of soaking in the treating solution and incorporating urea in the PF resin on the properties and formaldehyde emission of the treated wood were investigated. Wood strips of dimension 10mm x 50mm x 150mm (impreg) and 20mm x50mm x 150 mm (compreg) with initial MC of 15, 25 and >40% were impregnated with 15% LmwPF using a vacuum-pressure process. The samples were left soaked under pressure for 30, 60 and 120 min. The effect of the processing variables on the treatability of the wood was then analyzed. After impregnation, the treated samples were partially cured at 65 °C for 6 h and subsequently compressed to a compression ratio of 50% in a hot press maintained at 150±2 °C for 60 min. In the second part of the study, urea (formaldehyde catcher) at concentrations of 10, 20, and 30% (based on solid PF) were incorporated separately in the PF resin and these mixture were used as treating solution to treat the wood. The treatment without urea and untreated solid wood served as controls for comparison purposes. The results showed that the initial MC of the wood significantly (p<0.05) affected polymer retention (PR), while soaking time affected PR and weight percent gain (WPG) of the treated material. The highest PR and WPG were attained by samples with initial MC of 25%. For each initial MC group,soaking for 120 min yielded the highest PR and WPG. The results also showed that there is positive correlation between PR and WPG. For compreg sesenduk, initial MC significantly affects WPG while soaking time did not have any significant effect on WPG. The highest and the lowest WPG were at 15% and 40% of initial MC respectively. Statistical analyses board properties showed that WPG had positive correlation with density, and reduction in water absorption (Rabs), but negative correlation with thickness swelling when tested soaking distilled.